How do adults with a learning disability construct their relationships with support workers? A Foucauldian discourse analysis - Peacock‐Brennan, Sinead (Journal of family therapy, 2025)
The research was conducted as part of a master's degree in systemic psychotherapy. It was informed by my developing systemic practice alongside my work as a clinical psychologist in a community learning disability service. Data was collected from semi‐structured interviews transcribed near verbatim and analysed using Foucauldian discourse analysis. The analytic process considered discursive objects, wider discourse, action orientation, subject positions and subjectivity. Five constructions of the support worker relationship are presented, namely, the support worker relationship as professional, equal and shared, a thing that can be bought with money, a family and being watched/protected. These constructions were drawn from discourses regarding professionalism, independence, the law, equality and humanity, industry and economy, parenting and longevity, and impairment. Some constructions matched those in the literature. The list of constructions could be used as a therapeutic tool to consider how constructions might utilise different discourses to enable meanings, practices and positions to be adopted or abandoned.